2021
DOI: 10.1021/acs.biomac.1c00687
|View full text |Cite
|
Sign up to set email alerts
|

Photoprintable Gelatin-graft-Poly(trimethylene carbonate) by Stereolithography for Tissue Engineering Applications

Abstract: A new photo-processable hybrid copolymer based on gelatin-poly(trimethylene carbonate) (Gel-g-PTMCn) was elaborated and showed a promising potential as resin for stereolithography towards the fabrication of scaffold for tissue engineering. Various lengths of PTMC were grafted from gelatin using hydroxy and amino side groups of the constitutive amino acids. The characterization of resulting hybrid copolymers was fully investigated by quantitative NMR spectroscopy before rendering them photosensitive by methacry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…In 3D bioprinting, to meet the characteristics required by its manufacturing process, the materials used often use various biomedical materials, including synthetic polymers, natural polymers, and cells needed for printing. , This printable polymer solution, favorable for making a cell-laden construct to mimic the physiological structure, is called bioink. During or after printing it out, a suitable cross-linking mechanism is often needed to maintain the design and structure. To develop an ideal bioink, it is necessary to address its mechanical properties, rheological properties, and biological-related characteristics in the design to cope with the desired printed cells, which is critical for the printed microorgans. Therefore, to assess bioink feasibility, it is essential to understand the properties of the bioink before, during, and after gelation because it includes such aspects as the resolution of structure, cell viability, and shape fidelity. For example, Jia et al showed that the properties of the bioink like the viscosity and density of alginate-based material would affect the printability, so before 3D printing, it is necessary to evaluate the suitable range of bioink properties. , …”
Section: Introductionmentioning
confidence: 99%
“…In 3D bioprinting, to meet the characteristics required by its manufacturing process, the materials used often use various biomedical materials, including synthetic polymers, natural polymers, and cells needed for printing. , This printable polymer solution, favorable for making a cell-laden construct to mimic the physiological structure, is called bioink. During or after printing it out, a suitable cross-linking mechanism is often needed to maintain the design and structure. To develop an ideal bioink, it is necessary to address its mechanical properties, rheological properties, and biological-related characteristics in the design to cope with the desired printed cells, which is critical for the printed microorgans. Therefore, to assess bioink feasibility, it is essential to understand the properties of the bioink before, during, and after gelation because it includes such aspects as the resolution of structure, cell viability, and shape fidelity. For example, Jia et al showed that the properties of the bioink like the viscosity and density of alginate-based material would affect the printability, so before 3D printing, it is necessary to evaluate the suitable range of bioink properties. , …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, selecting carrier materials for biodegradable drug delivery systems is crucial for treating chronic osteomyelitis. Poly (trimethylene carbonate) (PTMC) is a polymer with excellent biocompatibility and good degradation properties, which has great potential in the fields of drug sustained release and tissue engineering (Dienel et al, 2019;Mohajeri et al, 2020;Weisgrab et al, 2020;Brossier et al, 2021). More importantly, Yang et al show that PTMC does not generate acidic degradation products during the degradation process (Yang et al, 2014;Yang et al, 2015;Yang et al, 2016;Hou et al, 2017;Hou et al, 2019;Cai et al, 2021;Hou et al, 2021) and is an ideal carrier material for biodegradable long-acting sustained-release implants (Yang et al, 2012;Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The micelles have a diameter in the range 20-40 nm, which can be estimated from the micrographs with the scale bars. The diameter obtain from TEM is lower than from DLS, which can be attributed to the dehydration and contraction of the micelles 27.…”
mentioning
confidence: 71%
“…Poly(trimethylene carbonate) (PTMC) is a biodegradable polycarbonate widely used in biomedical applications because of its good biocompatibility. [26][27][28] Compared with the classical polymers such as PLA, PLGA, PCL, PTMC has advantages of controllable mechanical property and degradation rate. 29 Besides, PTMC degrades in vivo by a surface erosion process, without the formation of acidic degradation products.…”
Section: Introductionmentioning
confidence: 99%